Recently graduated midwives in Uganda: Self-perceived achievement, wellbeing and work prospects. (March 2020) - Copestake, James; Theuss, Marc; Brownie, Sharon; Davies, Gabby; Burke, Eva; Mukuru, Moses; Kyakuwaire, Hellen; Edwards, Grace
Abstract: Objective: to investigate how recent graduates from a combined work/study midwifery degree programme in Uganda viewed its effects on their wellbeing and work prospects. Design: Using an adapted version of the Qualitative Impact Protocol (QuIP), a phenomenological approach was applied to thematic analysis to examine semi-structured interviews and WhatsApp group discussion. Setting: Introduction of enhanced midwifery training (from Diploma to Degree level) combining study with professional practice within a low income country health system facing extreme capacity constraints. Participants: 14 members of the first cohort of graduates from the degree programme. Findings: The graduates were overwhelmingly positive about improved professional knowledge, clinical skills, confidence, career commitment and prospects. They also had to contend with resentment from colleagues, increased workload and debt. Counselling training, peer support, and experience of managing stress during the training helped them to cope with these challenges. Conclusions: Qualitative feedback from those receiving advanced midwifery training highlights the importance of addressing social as well as technical skills, including leadership capacity and resilience in handling working relationships.